Improving Career Planning using Website-Based Career Information Service: Array - Hotma Rosalin Tumanggor; Sunawan Sunawan; Edy Purwanto (Islamic Guidance and Counseling Journal, 2018)
Career is a life long process. This study aims to improve the career planning of senior high school students in Tarakan City through information career services assistance through the website. The experimental design used in this research is quasi-experiment in the form of one group pretest-post design. The career planning scale consists of 45 items with 5 falling items and 0.875 alpha coefficient. This study involved 35 students as an experimental group selected by purposive sampling. The result of this research is career information service the website-assisted effectively improve the career planning of high school students in Tarakan City (10,094, p <0.01).